Strategi Pemasaran Sosial Komunitas Sosial Blood for Life - Nissa, Hairun; Ariyani, Nafiah (International Journal of Demos (IJD), 2023)
AbstractThis study aims to describe the social marketing strategy implemented by the Blood for Life community in changing people's behavior to donate blood. Lack of blood stock is a very crucial issue in Indonesia. Blood for life is a social community that voluntarily helps others who are in need of blood for free. Blood for Life is a network of links between people who need blood and people who will donate blood. The literature review used to support this research analysis is social marketing strategies and non-profit organizations. The research approach uses a descriptive qualitative approach with the case study method. The research data were obtained through in-depth trainers to research informants, namely the founders of the organization, administrators and volunteers. Other data were obtained through researchers' observations of Blood for Life as well as documentation and uploads of activities uploaded via the internet. The results of this study indicate that the stages in social marketing such as analyzing the social marketing environment and selecting target adopters are carried out by Blood for Life, but are not structured. However it does not interfere with Blood for Life social marketing and activity settings and organizations can adjust accordingly. Blood for Life is able to change the behavior of its members to be more positive through education on empathetic values given to target adopters. The most effective social marketing promotion strategies are used to get and change prioritized member behavior through social media. Personal belief in the founder of Blood for Life's social media has become an effective and successful promotion strategy.Keywords: Social Marketing Strategy, Social Community, Behavior Change AbstrakPenelitian ini bertujuan untuk mendeskripsikan strategi pemasaran sosial yang dilakukan oleh komunitas Blood for Life dalam mengubah perilaku masyarakat untuk mendonorkan darah. Kekurangan stok darah menjadi isu yang sangat krusial di Indonesia. Blood for life merupakan komunitas sosial yang secara sukarela membantu orang lain yang sedang membutuhkan darah secara cuma-cuma. Blood for Life menjadi jaringan penghubung antara orang yang membutuhkan darah, dengan orang yang akan mendonorkan darahnya. Kajian pustaka yang digunakan untuk mendukung analisis penelitian ini adalah strategi pemasaran sosial dan organisasi nirlaba. Pendekatan penelitian menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus. Data penelitian diperoleh melalui wawancara mendalam kepada informan penelitian yaitu pendiri organisasi, pengurus dan relawan. Data lainnya diperoleh melalui observasi peneliti terhadap Blood for Life serta dokumentasi dan unggahan kegiatan yang diunggah melalui internet. Hasil penelitian ini menunjukkan bahwa tahapan dalam pemasaran sosial seperti analyzing the social marketing environment dan selecting target adopter telah dilakukan oleh Blood for Life, akan tetapi tidak terstruktur. Namun tidak mengganggu jalannya pemasaran sosial dan aktivitas Blood for Life dan organisasi dapat menyesuaikan sesuai kebutuhannya. Blood for Life mampu mengubah perilaku anggotanya menjadi lebih positif melalui edukasi nilai-nilai empati yang diberikan kepada target adopter. Strategi promosi pemasaran sosial yang paling efektif digunakan untuk mendapatkan serta mengubah perilaku anggota diprioritaskan melalui media sosial. Adanya kepercayaan yang bersifat personal kepada media sosial pendiri Blood for Life menjadi strategi promosi yang efektif dan berhasil.Kata Kunci: Strategi Pemasaran Sosial, Komunitas Sosial, Perubahan Perilaku